PHYTOCHEMICAL AND ANTIMICROBIAL STUDIES ON GARCINIA LATTISSIMA MIQ. FRUIT EXTRACT - Ambarwati, Neneng Sitisilfi; Elya, Berna; Malik, Amarila; Hanafi, Muhammad (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present investigation was aimed to explore the phytoconstituents present in the fruit part of Garcinia lattissima Miq. and their antimicrobial efficacy. Methods: The preliminary phytochemical constituents were qualitatively analyzed using the standard procedures described in Materia Medica Indonesia. Antimicrobial screening was performed using disc diffusion and dilution methods. Results: Phytochemical screening of different extracts of G. lattissima Miq. fruits revealed the presence of tannins, saponins, flavonoids, and alkaloids, and the results are shown in Table 1. The ethyl acetate and methanolic extracts of G. lattissima Miq. fruits showed antimicrobial activity, and the n-hexane extract failed to prove the inhibition against the selected pathogens. Conclusion: The results of the phytochemical and bio-efficacy study revealed most valuable information and also support the continued sustainable use of G. lattissima Miq. fruits in the traditional system of medicine.